A carbazole–triphenylamine copolymer‐bearing pendant europium complexes: Synthesis and luminescence properties. Issue 46 (1st September 2015) - Jin, Yuxia; Zuo, Weiwei; Gao, Hongyan; Fu, Linfeng; Liu, Yingliang; Wu, Wenbo; Xu, Shengang; Cao, Shaokui
ABSTRACT A novel carbazole–triphenylamine copolymer‐bearing pendant bipyridine PM1TPA and corresponding europium (III) complexed polymer PM1TPA–Eu–x, in which the values of x are 0.1, 0.5, and 1.0 representing the molar ratio of bipyridine ligands complexed with Eu(III), were designed and synthesized. Their chemical structures were confirmed by 1H NMR, FT‐IR, and elemental analysis. Both PM1TPA and PM1TPA–Eu shows good solubility in common organic solvents such as tetrahydrofuran (THF) and CHCl3. The 5% weight loss temperature (Td5%) of PM1TPA and PM1TPA–Eu–1.0 are 363oC and 306oC, respectively. The photoluminescence (PL) spectra of PM1TPA–Eu in solution consists of two emission bands, one in the 400–570 nm region and another at 612 nm, corresponding to the emission of polymer main chain and europium complexes, respectively. When the concentration of PM1TPA–Eu–1.0 in THF solution increases, the PL intensity in the 400–570 nm regions became more and more weaker. And only the characteristic emission of europium complex was observed in the solid film, which indicates that the excited energy absorbed by the polymer backbone was efficiently transferred to the europium complexes. Furthermore, nearly monochromatic red electroluminescence from europium complex was observed from the polymeric light‐emitting diode using PM1TPA–Eu–1.0 as the emissive layer under 25 V forward bias. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42746.